Invitation games: An experimental approach to coalition formation - Takaaki Abe; Yukihiko Funaki; Taro Shinoda (Games, 2021)
This paper studies how to form an efficient coalitionda group of people. More specifically, we compare two mechanisms for forming a coalition by running a laboratory experiment and reveal which mechanism leads to higher social surplus. In one setting, we invite the subjects to join a meeting simultaneously, so they cannot know the other subjects' decisions. In the other setting, we ask them sequentially, which allows each subject to know his or her predecessor's choice. Those who decide to join the meeting form a coalition and earn payoffs according to their actions and individual preferences. As a result, we obtain the following findings. First, the sequential mechanism induces higher social surplus than the simultaneous mechanism. Second, most subjects make choices consistent with the subgame-perfect Nash equilibrium in the sequential setting and choose the dominant strategy in the simultaneous setting, when a dominant strategy exists. Finally, when the subjects need to look further ahead to make a theoretically rational choice, they are more likely to fail to choose rationally.
Keywords: 330; coalition formation; laboratory experiment; non-cooperative games